Interaction of CD38 Variant and Chronic Interpersonal Stress Prospectively Predicts Social Anxiety and Depression Symptoms Over 6 Years. (January 2016) - Tabak, Benjamin A.; Vrshek-Schallhorn, Suzanne; Zinbarg, Richard E.; Prenoveau, Jason M.; Mineka, Susan; Redei, Eva E.; Adam, Emma K.; Craske, Michelle G.
Variation in the CD38 gene, which regulates secretion of the neuropeptide oxytocin, has been associated with several social phenotypes. Specifically, rs3796863 A allele carriers have demonstrated increased social sensitivity. In 400 older adolescents, we used trait-state-occasion modeling to investigate how rs3796863 genotype, baseline ratings of chronic interpersonal stress, and their gene–environment (G×E) interaction predicted trait social anxiety and depression symptoms over 6 years. We found significant G×E effects for CD38 A-carrier genotypes and chronic interpersonal stress at baseline predicting greater social anxiety and depression symptoms. A significant G×E effect of smaller magnitude was also found for C/C genotype and chronic interpersonal stress predicting greater depression; however, this effect was small compared with the main effect of chronic interpersonal stress. Thus, in the context of chronic interpersonal stress, heightened social sensitivity associated with the rs3796863 A allele may prospectively predict risk for social anxiety and (to a lesser extent) depression.